Characterization of Influences of Steel-Aluminum Dissimilar Joints with Intermediate Zinc Layer - Tobias Bick; Verena Heuler; Kai Treutler; Volker Wesling (Metals, 2020)
Brittle intermetallic phases are formed when steel and aluminum are joined. Therefore, it is difficult to use this combination of materials when applying the multimaterial design in the construction of load-adapted and weight-adapted structures. In order to largely avoid the formation of these brittle phases, joining processes based on diffusion processes, such as composite forging, depict a good solution approach. The materials are joined in a solid state. Furthermore, zinc additives are used to create the joint. Zinc forms a compound with both steel and aluminum without the formation of brittle phases. By combining the composite forging process with zinc additives, strength values of 26 N/mm2 can be reached. This is higher, in comparison to former investigations of resistance spot welded and clinched joints. The joint properties depend on the composition of the zinc interlayer. Small amounts of magnesium in the zinc interlayer affected the strength and ductility values. While the strength decreased by about 30% in contrast to the zinc layer without magnesium, the ductility increased by 60%. This effect was probably due to the metallurgical impact of the alloying elements on phase formation, as could be shown by energy dispersive X-ray spectroscopy (EDX) analyses of the joint zones. Thereby, it was shown that the brittle intermetallic phases are located only in small areas.